A moderated mediation model of despotic leadership and knowledge sabotage behavior - Usman, Muhammad; Garavan, Thomas; Karatepe, Osman M.; Akhtar, Muhammad Waheed; Rescalvo-Martin, Elisa; Aslam, Muhammad Kashif (Elsevier Sci Ltd, 2025)
Our paper develops and tests a moderated mediation model of despotic leadership (DL) and knowledge sabotage behavior (KSB). The model assesses: (a) the link between DL and KSB; (b) emotional dissonance as a mediator between DL and KSB; (c) willpower and waypower as the two moderators of the effect of DL on the aforesaid undesirable outcome; and (d) willpower and waypower as the two moderators of the effect of DL on KSB via emotional dissonance. To gauge these relationships, we used time-lagged data obtained from hotel frontline employees. Most of the hypothesized associations are supported, and the model we proposed is viable. Managers' DL heightens employees' KSBs, and emotional dissonance mediates this link. FLEs' waypower reduces the detrimental effect of DL on KSB. Waypower also mitigates the deleterious effect of DL on the said outcome via emotional dissonance.
Keywords: Despotic leadership; Emotional dissonance; Frontline employees; Hope; Knowledge sabotage; Waypower; Willpower